2019
DOI: 10.1007/s10815-019-01430-z
|View full text |Cite
|
Sign up to set email alerts
|

Double chromosomal translocation in an infertile man: one-step FISH meiotic segregation analysis and reproductive prognosis

Abstract: Background The prevalence of chromosomal translocations is 1/500 in the general population. While in the vast majority of cases, carriers have a normal phenotype; they can present with difficulty conceiving due to the presence of a proportion of unbalanced gametes as a consequence of abnormal chromosomal segregation during meiosis. Since complex translocations involve three or more chromosomes, meiotic segregation leads to a greater number of possible combinations which effectively complicate both their study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
(15 reference statements)
1
3
0
Order By: Relevance
“…Pierron et al [15] and our results have shown that both sperm preparation methods show a similar distribution of alternate and adjacent sperm.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Pierron et al [15] and our results have shown that both sperm preparation methods show a similar distribution of alternate and adjacent sperm.…”
Section: Discussionsupporting
confidence: 81%
“…So far, there were five cases of male RobT carriers t(21;22) described in the literature [6,10,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…In the general population, balanced chromosomal rearrangements which include reciprocal translocation and Robertsonian translocation have a prevalence of about 1/500 (Pierron et al, 2019). The prevalence in male with azoospermic or severe oligozoospermia, and couples with a history of IVF failure and recurrent miscarriage reaching 1.4% and 2.2%, respectively (Clementini et al, 2005;Liu et al, 2013;Zhang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Oskar A. Haas, St. Anna Children's Hospital, Austria also be called double rearrangement (Madan, 2013;Pierron et al, 2019). CCR carriers have a higher risk of unbalanced chromosomes developing in their gametes (Escudero et al, 2008).…”
Section: Open Access Edited Bymentioning
confidence: 99%